2022
DOI: 10.1039/d2bm00539e
|View full text |Cite
|
Sign up to set email alerts
|

CaCO3-based carriers with prolonged release properties for antifungal drug delivery to hair follicles

Abstract: Superficial fungal infections are of serious concern worldwide due to their morbidity and increasing distribution across the globe in this era of growing antimicrobial resistance. Delivery of antifungals to target...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 143 publications
(222 reference statements)
7
38
0
Order By: Relevance
“…Here, local diffusion of the 5(6)-carboxyfluorescein into the gel over the entire coating area was detected. Note that, apart from robust triggering to open the microchambers, the ultrasound also facilitated the penetration of substances [ 32 , 33 , 34 ] and particles [ 35 , 36 , 37 , 38 ] into the biological tissues and structures. Balloon inflation without ultrasonic treatment did not lead to such visible gel staining ( Figure 2 G).…”
Section: Resultsmentioning
confidence: 99%
“…Here, local diffusion of the 5(6)-carboxyfluorescein into the gel over the entire coating area was detected. Note that, apart from robust triggering to open the microchambers, the ultrasound also facilitated the penetration of substances [ 32 , 33 , 34 ] and particles [ 35 , 36 , 37 , 38 ] into the biological tissues and structures. Balloon inflation without ultrasonic treatment did not lead to such visible gel staining ( Figure 2 G).…”
Section: Resultsmentioning
confidence: 99%
“…Vaterite particles represent prospective carriers for drug delivery as providing biocompatibility, biodegradability, high payload ability, and low prime cost. The efficiency of their application as drug carriers was multiply demonstrated for the delivery of a wide range of therapeutic agents, such as proteins, enzymes, , and high and low molecular drugs, , including water poorly soluble antifungal ones. Various delivery routes were shown suitable for their transportation . Importantly, it has been convincingly demonstrated that the use of vaterite carriers enabled the delivery of encapsulated substances into the hair follicles upon their topical application. , Previous studies have also revealed the high potential of vaterite particles for intracellular drug delivery. Vaterite represents one of the crystalline modifications of calcium carbonate (CaCO 3 ) .…”
mentioning
confidence: 99%
“…Importantly, it has been convincingly demonstrated that the use of vaterite carriers enabled the delivery of encapsulated substances into the hair follicles upon their topical application. , Previous studies have also revealed the high potential of vaterite particles for intracellular drug delivery. Vaterite represents one of the crystalline modifications of calcium carbonate (CaCO 3 ) . This polymorph is porous and metastable; thus, the cargo release from vaterite particles in various media is driven by their dissolution either during the recrystallization to calcite , or during the degradation. , The rate of these processes strongly depends on the surrounding conditions (such as pH, temperature or ionic strength of the media, presence of different ions or additives, ,,, system’s openness/closedness) and the parameters of the carrier itself (size, shape, presence of a covering shell, structure of a covering shell ,, ). Particularly, low pH values of media accelerate the dissolution of vaterite particles, while protein adsorption on their surface significantly inhibits both dissolution and recrystallization processes resulting in a slower drug release rate .…”
mentioning
confidence: 99%
See 2 more Smart Citations